AI-Assisted Failure Location Platform for Optical Network - Pengcheng Liu; Wei Ji; Qiang Liu; Xuwei Xue (International Journal of Optics)
In the paper, we applied the customized AI module to the OTDR device and, combined with the optical power monitoring module, realized the AI-assisted optical network fault location mechanism for the high-density interconnection scenario of data centers. The mechanism can make full use of the data from optical links. Based on the link data, the AI module can predict the links that may fail, and then the target links will be monitored by the optical power module. The mechanism can quickly locate and respond to faulty links. Through the test, the introduction of an AI model can improve the average fault detection efficiency of the link by 98.41%.